Analisa Kerentanan Hunian Tetap di Kabupaten Cianjur dengan Evaluasi Probabilitas Percepatan Gerakan Tanah - Syamsi, Muhammad Ibnu; Faizah, Restu; Monika, Fanny; Wicaksono, Imam (AGREGAT, 2024)
Indonesia is one of the countries that has a fairly high seismic condition. This is because Indonesia is passed by the Pacific Ring of Fire, which brings together many world plates, so it is natural that many earthquakes occur in Indonesia. With a fairly high seismic condition, there is a need for vigilance and actions taken to overcome the situation. The infrastructure sector becomes an important spotlight when an earthquake occurs because casualties are often caused by structural failures that are not strong enough to withstand the earthquake load. This is similar to what happened in the earthquake in Cianjur in 2022, which claimed many lives due to the numerous structural failures in permanent residences. Therefore, this research was conducted to evaluate the permanent residences of the community related to the vulnerability that occurred due to the earthquake. Building vulnerability testing is carried out using the Incremental Dynamic Analysis (IDA) method with data from 11 earthquake records. Later, the building’s response to the earthquake load will be obtained, and the probability of damage seen from the vulnerability curve will be known. The five performance levels of the building are Operational Phase (OP), Immediate Occupancy (IO), Damage Control (DC), Life Safety (LS), and Collapse Prevention (CP).